Muslim-friendly ecotourism in halal industry ecosystem : an exploratory study in Karimunjawa - Saffinee, Siti Syahirah; Jamaludin, Mohd Aizat; Ramli, Mohd Anuar; Al-Baarri, Ahmad Ni'maytullah (HH Publisher, 2019)
Muslim friendly tourism (MFT) has been introduced to accommodate the religious tourism that consistent with Islamic teaching. In order to build consumer’s confidence and certainly, the particular standard focusing on MFT (MS2610:2015) was launched in 2015. Responding to the Strategic Roadmap for Development of Islamic Tourism in OIC member Countries (2017), developing sub-niche markets in Islamic tourism sector such as ecotourism activities with halal sensitivity need to be improve on their hospitality of the products and services. However, concerns have been raised on the potential of the Karimunjawa Islands to be assessed and implement as Muslim friendly ecotourism (MFET). Hence, this paper aim to study on MFET based on secondary data, interviews and field observation. The research result shows that knowledge on ecotourism concept was not an issue among informants. However, the level of understanding on MFT is still low. This study conducts a qualitative research with community and physical settings in Karimunjawa Islands. The study subjects consisted travel agent, homestay and fisherman. Data retrieved through interview and participant observation. This should lead to an understanding that implementation of MFT concept is not just to propose the new product and services but, more so, to practice of Shariah compliance in ecotourism ecosystem.